Social network and HIV/AIDS: A bibliometric analysis of global literature - Doan, Linh Phuong; Nguyen, Long Hoang; Auquier, Pascal; Boyer, Laurent; Fond, Guillaume; Nguyen, Hien Thu; Latkin, Carl A.; Vu, Giang Thu; Hall, Brian J.; Ho, Cyrus S. H.; Ho, Roger C. M. (Frontiers in Public Health, 2022)
Social networks (SN) shape HIV risk behaviors and transmission. This study was performed to quantify research development, patterns, and trends in the use of SN in the field of HIV/AIDS, and used Global publications extracted from the Web of Science Core Collection database. Networks of countries, research disciplines, and most frequently used terms were visualized. The Latent Dirichlet Allocation method was used for topic modeling. A linear regression model was utilized to identify the trend of research development. During the period 1991–2019, in a total of 5,698 publications, topics with the highest volume of publications consisted of (1) mental disorders (16.1%); (2) HIV/sexually transmitted infections prevalence in key populations (9.9%); and (3) HIV-related stigma (9.3%). Discrepancies in the geographical distribution of publications were also observed. This study highlighted (1) the rapid growth of publications on a wide range of topics regarding SN in the field of HIV/AIDS, and (2) the importance of SN in HIV prevention, treatment, and care. The findings of this study suggest the need for interventions using SN and the improvement of research capacity via regional collaborations to reduce the HIV burden in low- and middle-income countries.